2020
DOI: 10.1111/ajt.15790
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic and radiologic assessment of nontransplanted donor lungs

Abstract: Donor organ shortage results in significant waiting list mortality. Donor lung assessment is currently based on donors’ history, gas exchange, chest X‐ray, bronchoscopy findings, and ultimately in situ inspection but remains subjective. We correlated histopathology and radiology in nontransplanted donor lungs with the clinical indications to decline the offered organ. Sixty‐two donor lungs, not used for transplantation (2010‐2019), were procured, air‐inflated, frozen, scanned with computed tomography, systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Vanstapel et al demonstrated a histopathologic evaluation of the donor lungs declined for transplantation. They reported that 3 of 23 (13.0%) donor lungs that were not transplanted due to extrapulmonary causes displayed severe histologic abnormalities (pneumonia, emphysema) [10]. Similar to their study, 3 of 23 cases (13.0%) in the BLT control group and in 2 of 26 cases (7.7%) in the SLT control group showed infiltrations in EVL-CT in our study.…”
Section: Plos Onesupporting
confidence: 89%
“…Vanstapel et al demonstrated a histopathologic evaluation of the donor lungs declined for transplantation. They reported that 3 of 23 (13.0%) donor lungs that were not transplanted due to extrapulmonary causes displayed severe histologic abnormalities (pneumonia, emphysema) [10]. Similar to their study, 3 of 23 cases (13.0%) in the BLT control group and in 2 of 26 cases (7.7%) in the SLT control group showed infiltrations in EVL-CT in our study.…”
Section: Plos Onesupporting
confidence: 89%
“…In our previous work, we obtained CT scans from declined donor lungs and found that CT examination of these specimens by a trained thoracic radiologist provided detailed information of interstitial changes otherwise obscured during routine donor lung assessment. 12,13 However, manual screening of CT scans is hampered by interobserver variability, as well as delays due to accessibility to radiologists. Importantly, time constraints must be minimized to effectively incorporate our strategy of applying CT scanning to donor lung screening.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 29, 2023. ; https://doi.org/10.1101/2023.03.28.23287705 doi: medRxiv preprint 13 An important attribute of our ML screening method is its ability to focus exclusively on the features presented in CT scans without requiring additional information such as donor or recipient characteristics or clinical data. Due to the novelty of our method, i.e., using clinical CT scans to screen donor lungs, our data came only from this single center study.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Finally, it is possible that the timing of ALAD may impact outcomes, with early-onset ALAD having a more favorable prognosis. 27 Our series included patients with both early and late (>2-3 mo posttransplant) ALAD, which may in part account for our improved outcomes compared to other cohorts with severe ALAD ("lung white out"). Despite the heterogeneity in severe ALAD onset, we did not appreciate superior outcomes in those with early disease.…”
Section: Discussionmentioning
confidence: 99%